AKTIVITAS ANTIBIOFILM DAN ANTIBAKTERI DAUN BINAHONG (Anredera cordifolia (Ten) Steenis) TERHADAP Pseudomonas aeruginosa - Fradine, Chossy; Ismi Rahmawati; Opstaria Saptarini (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Plant in Indonesia that has antibacterial activity is binahong (Anredera cordifolia (Ten.) Stennis). Binahong leaf contains flavonoid, saponins, tannins and terpenoids compounds. The purpose of the study are determining the potential of extracts and fractions (n-hexane, ethyl acetate and water) in inhibiting the formation of biofilms, biofilm degradation and the value of P. aeruginosa bacterial MBC and to determining the working location of the most active binahong leaf fraction. Binahong leaf is extracted by using maceration method with ethanol as solvent. Then the viscous extract is fractionated with n-hexane, ethyl acetate and water. Antibiofilm activity test is carried out using a microplate and absorbance readings using a microplate reader at a wavelength of 595 nm. The antibacterial activity test uses the dilution method. The IC50 value of the biofilm inhibition test on the extract, water fraction, ethyl acetate and n-hexane for P.aeruginosa bacteria was 0,94; 1,21; 1,03; 0,78. The EC50 value of the biofilm degradation test on the extract, n-hexane, ethyl acetat, water e for P. aeruginosa bacteria is 10,95; 16,06; 12,35; 5,92. The minimum bactericidal concentration value of binahong leaf water fraction for P. aeruginosa is 512 mg/ml.